Electric fields control the orientation of peptides irreversibly immobilized on radical-functionalized surfaces - Lewis J. Martin (Nature Portfolio, 2018)
Implanted materials can be rejected by the body, and coating the surfaces with peptides is seen as an option to overcome this problem. Here, the authors investigated how pH and electric fields can be used to prepare defined peptide coatings.